Detection of spondylosis deformans in thoracolumbar and lumbar lateral X-ray images of dogs using a deep learning network - Park, Junseol; Cho, Hyunwoo; Ji, Yewon; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2024)
Spondylosis deformans is a noninflammatory osteophytic reaction that develops to re-establish the stability of weakened joints between intervertebral discs. However, assessing these changes using radiography is subjective and difficult. In human medicine, attempts have been made to use artificial intelligence to accurately diagnose difficult and ambiguous diseases in medical imaging. Deep learning, a form of artificial intelligence, is most commonly used in medical imaging data analysis. It is a technique that utilises neural networks to self-learn and extract features from data to diagnose diseases. However, no deep learning model has been developed to detect vertebral diseases in canine thoracolumbar and lumbar lateral X-ray images. Therefore, this study aimed to establish a segmentation model that automatically recognises the vertebral body and spondylosis deformans in the thoracolumbar and lumbar lateral radiographs of dogs. Methods: A total of 265 thoracolumbar and lumbar lateral radiographic images from 162 dogs were used to develop and evaluate the deep learning model based on the attention U-Net algorithm to segment the vertebral body and detect spondylosis deformans. Results: When comparing the ability of the deep learning model and veterinary clinicians to recognise spondylosis deformans in the test dataset, the kappa value was 0.839, indicating an almost perfect agreement. Conclusions: The deep learning model developed in this study is expected to automatically detect spondylosis deformans on thoracolumbar and lumbar lateral radiographs of dogs, helping to quickly and accurately identify unstable intervertebral disc space sites. Furthermore, the segmentation model developed in this study is expected to be useful for developing models that automatically recognise various vertebral and disc diseases.